Co(Ⅱ)-PIIMs materials and preparation methods for selective adsorption of cobalt ions

Co(Ⅱ)-SIM-IIP is combined with polymers through electrospinning technology to prepare selective and highly hydrophilic Co(Ⅱ)-PIIMs materials, which solves the problem of insufficient mechanical stability of existing MOFs adsorbents. and difficult recovery problems, achieving efficient cobalt ion adsorption and recovery.

CN117942951BActive Publication Date: 2025-01-21CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410060661.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2025-01-21
Estimated Expiration
2044-01-16

AI Technical Summary

Technical Problem

The application of ion-blotting adsorbents based on MOFs in the prior art is limited in water repair due to insufficient mechanical stability, high manufacturing cost and difficulty in handling and recycling.

Method used

Using zinc acetate, methanol, 4-methyl-5-imidazole formaldehyde, tetrahydrofuran, tetraethylenepentamine, cobalt nitrate hexahydrate, dimethylformamide, polytetrafluoroethylene, epichlorohydrin, polyacrylonitrile powder and poly Co(Ⅱ)-PIIMs materials are prepared from ingredients such as vinylpyrrolidone, and are combined with polymers through electrospinning technology to form selective Co(Ⅱ)-PIIMs materials.

Benefits of technology

Co(II)-SIM-IIP is evenly dispersed on the nanofibers through electrospinning technology, which enhances the hydrophilicity, selectivity and separation ability of cobalt ions of the membrane material, and solves the problem of difficult recycling of adsorbed materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117942951B_ABST
    Figure CN117942951B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of adsorption technology, and specifically discloses a Co(II)-PIIMs material and preparation method for selective adsorption of cobalt ions, comprising the following components: zinc acetate, methanol, 4-methyl-5-imidazole carboxaldehyde, tetrahydrofuran, tetraethylene pentamine, cobalt nitrate hexahydrate, dimethylformamide, polytetrafluoroethylene, epichlorohydrin, polyacrylonitrile powder and polyvinylpyrrolidone. An intermediate is prepared by aldehyde-amine condensation reaction of SIM-1 and the amino groups on tetraethylene pentamine, at which time the nitrogen of tetraethylene pentamine chelates with cobalt, cross-links with propylene oxide, and elution of cobalt by nitric acid to obtain Co(II)-SIM-IIP, and then selective Co(II)-PIIMs are prepared by electrostatic spinning technology, Co(II)-SIM-IIP is combined with a polymer by electrostatic spinning technology, and Co(II)-SIM-IIP is uniformly dispersed on nanofibers, thereby enhancing the hydrophilicity, selectivity and separation ability of membrane materials for cobalt ions, and solving the problem that the adsorption material is not easy to be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adsorption technology, and in particular to a Co(II)-PIIMs material for selectively adsorbing cobalt ions and a preparation method thereof. Background Art

[0002] At present, heavy metals are widely regarded as environmental pollutants due to their toxicity and non-biodegradability, causing serious harm to ecosystems and human health. Among them, cobalt is not only one of the most widely used metals, but also an important component of strategic resources. Due to the large-scale use of cobalt in industry, a large amount of cobalt-containing wastewater will inevitably be produced. It is not advisable to release Co (II) into the water body. Intake of high levels of Co (II) may cause serious health problems including cancer.

[0003] In the prior art, Co (II) is treated by ion exchange, chemical precipitation, adsorption and membrane separation. Among the above methods, membrane-based adsorption has the advantages of being economical, flexible in continuous operation, easy to scale up, and can be integrated into other adsorption methods.

[0004] However, in the prior art, the application of MOFs-based ion-imprinted adsorbents in water remediation is limited due to insufficient mechanical stability, high manufacturing cost, and difficulty in handling and recycling. Summary of the invention

[0005] The purpose of the present invention is to provide a Co(Ⅱ)-PIIMs material and a preparation method for selectively adsorbing cobalt ions, aiming to solve the technical problem that the application of MOFs-based ion imprinted adsorbents in water remediation is limited due to insufficient mechanical stability, high manufacturing cost, and difficulty in processing and recycling.

[0006] To achieve the above object, the present invention adopts a Co(II)-PIIMs material for selectively adsorbing cobalt ions, comprising the following components:

[0007] Zinc acetate, methanol, 4-methyl-5-imidazolecarboxaldehyde, tetrahydrofuran, tetraethylenepentamine, cobalt nitrate hexahydrate, dimethylformamide, polytetrafluoroethylene, epichlorohydrin, polyacrylonitrile powder and polyvinylpyrrolidone.

[0008] The present invention also provides a method for preparing a Co(II)-PIIMs material for selectively adsorbing cobalt ions. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions as described above comprises the following steps:

[0009] Dissolve zinc acetate in methanol, dissolve 4-methyl-5-imidazolecarboxaldehyde in tetrahydrofuran, mix the mixed solution of zinc acetate and methanol and the mixed solution of 4-methyl-5-imidazolecarboxaldehyde and tetrahydrofuran, stir vigorously at room temperature for 24 hours, centrifuge, wash with methanol, and air-dry the obtained SIM-1 at room temperature for 48 hours;

[0010] Tetraethylenepentamine and cobalt nitrate hexahydrate were dissolved in dimethylformamide, heated under reflux at 70°C for 6h to allow tetraethylenepentamine to fully complex with cobalt ions, and then SIM-1 was added, and after being evenly dispersed, it was transferred to a hydrothermal reactor with polytetrafluoroethylene, and reacted at 120°C for 24h. After the reaction was completed, it was transferred to a flask, 0.25mL of epichlorohydrin was added, and heated under reflux at 70°C for 4h to complete the cross-linking reaction. Finally, the adsorbent was recovered by centrifugation, and the template cobalt ions were removed by washing with nitric acid. The material was washed with deionized water until neutral, and then vacuum dried to obtain tetraethylenepentamine functionalized MOFs cobalt ion imprinted polymer Co(Ⅱ)-SIM-IIP;

[0011] Tetraethylenepentamine was dissolved in dimethylformamide, heated under reflux at 70°C for 6h to fully complex tetraethylenepentamine with cobalt ions, and then SIM-1 was added, and after being evenly dispersed, it was transferred to a hydrothermal reactor with polytetrafluoroethylene, and reacted at 120°C for 24h. After the reaction was completed, it was transferred to a flask, 0.25mL of epichlorohydrin was added, and heated under reflux at 70°C for 4h to complete the cross-linking reaction. Finally, the adsorbent was recovered by centrifugation, and the template cobalt ions were removed by washing with nitric acid. The material was washed with deionized water until neutral, and then vacuum dried to obtain a tetraethylenepentamine functionalized nonionic imprinted polymer SIM-NIP.

[0012] Polyacrylonitrile powder, polyvinyl pyrrolidone and Co(Ⅱ)-SIM-IIP were dissolved in dimethylformamide and stirred at room temperature for 2 hours to prepare electrospinning precursor solution. The electrospinning precursor solution was dried in a vacuum drying oven at 60°C for 6 hours, transferred into deionized water, and polyvinyl pyrrolidone was eluted to obtain ion imprinted membrane material Co(Ⅱ)-PIIMs-x, x=8, 10, 12;

[0013] Polyacrylonitrile powder, polyvinyl pyrrolidone and SIM-NIP were dissolved in dimethylformamide and stirred at room temperature for 2 hours to prepare an electrospinning precursor solution. The electrospinning precursor solution was dried in a vacuum drying oven at 60°C for 6 hours, transferred to deionized water, and the polyvinyl pyrrolidone was eluted to obtain the non-ionic imprinted membrane material PNIMs-10.

[0014] Wherein, the amount of zinc acetate used is 9.5 g, the amount of 4-methyl-5-imidazolecarboxaldehyde used is 9.5 g, the amount of methanol used is 36 mL, and the amount of tetrahydrofuran used is 72 mL.

[0015] Wherein, the dosage of SIM-1 is 2.8 g, the dosage of cobalt nitrate hexahydrate is 2.9 g, the dosage of tetraethylenepentamine is 4.0 mL, and the dosage of dimethylformamide is 100 mL.

[0016] Among them, the molecular weight of polyacrylonitrile is 150000, the polyvinyl pyrrolidone is K30, the dosage of polyacrylonitrile and polyvinyl pyrrolidone is 0.5g, the dosage of Co(Ⅱ)-SIM-IIP is any one of 0.5g, 0.7g and 0.8g, and the parameters of electrospinning are: spinning voltage is 18kV, metal needle specification is 20G, casting liquid capacity of two syringes is 2mL, pushing speed is 0.0020mm / s, injection distance is 12cm, receiving speed is 150r / min.

[0017] The evaluation process of the membrane performance of Co(II)-PIIMs-x comprises the following steps:

[0018] The test was conducted using a membrane flux tester with a cross-flow filtration system. The pressure of the tester was adjusted to 1 bar, and the filter membrane was pre-pressed with deionized water at room temperature for 0.5 h to ensure a stable flux.

[0019] Under the above test conditions, deionized water was passed through the filter membrane for 0.25 h, and the pure water flux of the prepared Co(Ⅱ)-PIIMs-x was determined by collecting the volume of filtered deionized water;

[0020] Under the above pressure conditions, the membrane's Co(II) filtration performance was evaluated at a constant concentration of 50 mg / L of Co(II).

[0021] Among them, the evaluation of the adsorption performance of Co(Ⅱ)-PIIMs-x on cobalt ions includes the following steps: taking 100 mL of cobalt-containing wastewater with a concentration of 10 mg / L, adjusting the pH value to 5~9 with 1.0 mol / L NaOH solution, and then adding 10 mg of Co(Ⅱ)-PIIMs-x, and adsorbing the cobalt ions in the wastewater at a temperature of 288.15K~318.15K, and the adsorption treatment time is 0~24h.

[0022] Wherein, the pH value of the cobalt-containing wastewater is adjusted to 8.3.

[0023] Wherein, the adsorption temperature of the Co(Ⅱ)-PIIMs-x is 298.15K.

[0024] Among them, the adsorption time of the cobalt-containing wastewater is 12 hours.

[0025] The Co(II)-PIIMs material and preparation method for selectively adsorbing cobalt ions of the present invention have the following beneficial effects: an intermediate is prepared by aldehyde-amine condensation reaction between SIM-1 and the amino group on tetraethylenepentamine, wherein nitrogen of tetraethylenepentamine chelates with cobalt, cross-linked with propylene oxide, and cobalt is eluted by nitric acid to obtain Co(II)-SIM-IIP, and then selective Co(II)-PIIMs are prepared by electrostatic spinning technology, and Co(II)-SIM-IIP is combined with a polymer by electrostatic spinning technology, and Co(II)-SIM-IIP is uniformly dispersed on nanofibers, thereby enhancing the hydrophilicity, selectivity and separation ability of the membrane material for cobalt ions, and solving the problem that the adsorption material is not easy to be recycled. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 These are XRD analysis diagrams of PAN, SIM-1, Co(II)-SIM-IIP, SIM-NIP, Co(II)-PIIMs-10 and PNIMs-10 prepared by the present invention.

[0028] Figure 2 PAN and Co(II)-PIIMs-10 prepared in the present invention are SEM images.

[0029] Figure 3 It is the contact angle spectrum of PAN and Co(II)-PIIMs-x prepared by the present invention.

[0030] Figure 4 The membrane flux and retention rate of PAN and Co(II)-PIIMs-10 prepared by the present invention are

[0031] Figure 5 This is a diagram showing the effect of different pH values ​​on the adsorption of cobalt ions by PAN, SIM-1, Co(II)-SIM-IIP, SIM-NIP, and Co(II)-PIIMs-10 in the present invention.

[0032] Figure 6 This is a diagram showing the effect of different adsorption times on the adsorption of cobalt ions by Co(II)-PIIMs-10 and PNIMs-10 in the present invention.

[0033] Figure 7This is a diagram showing the effect of different cobalt ion concentrations on the adsorption of cobalt ions by Co(II)-PIIMs-10 and PNIMs-10 in the present invention.

[0034] Figure 8 This is a diagram showing the effect of different ions on the adsorption of cobalt ions by Co(II)-PIIMs-10 in the present invention.

[0035] Fig. 9 This is a diagram showing the effect of different temperatures on the adsorption of cobalt ions by Co(II)-PIIMs-10 in the present invention. DETAILED DESCRIPTION

[0036] The present invention provides a Co(II)-PIIMs material for selectively adsorbing cobalt ions, comprising the following components:

[0037] Zinc acetate, methanol, 4-methyl-5-imidazolecarboxaldehyde, tetrahydrofuran, tetraethylenepentamine, cobalt nitrate hexahydrate, dimethylformamide, polytetrafluoroethylene, epichlorohydrin, polyacrylonitrile powder and polyvinylpyrrolidone.

[0038] The present invention also provides a method for preparing a Co(II)-PIIMs material for selectively adsorbing cobalt ions. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions as described above comprises the following steps:

[0039] Dissolve zinc acetate in methanol, dissolve 4-methyl-5-imidazolecarboxaldehyde in tetrahydrofuran, mix the mixed solution of zinc acetate and methanol and the mixed solution of 4-methyl-5-imidazolecarboxaldehyde and tetrahydrofuran, stir vigorously at room temperature for 24 hours, centrifuge, wash with methanol, and air-dry the obtained SIM-1 at room temperature for 48 hours;

[0040] Tetraethylenepentamine and cobalt nitrate hexahydrate were dissolved in dimethylformamide, heated under reflux at 70°C for 6h to allow tetraethylenepentamine to fully complex with cobalt ions, and then SIM-1 was added, and after being evenly dispersed, it was transferred to a hydrothermal reactor with polytetrafluoroethylene, and reacted at 120°C for 24h. After the reaction was completed, it was transferred to a flask, 0.25mL of epichlorohydrin was added, and heated under reflux at 70°C for 4h to complete the cross-linking reaction. Finally, the adsorbent was recovered by centrifugation, and the template cobalt ions were removed by washing with nitric acid. The material was washed with deionized water until neutral, and then vacuum dried to obtain tetraethylenepentamine functionalized MOFs cobalt ion imprinted polymer Co(Ⅱ)-SIM-IIP;

[0041] Tetraethylenepentamine was dissolved in dimethylformamide, heated under reflux at 70°C for 6h to fully complex tetraethylenepentamine with cobalt ions, and then SIM-1 was added, and after being evenly dispersed, it was transferred to a hydrothermal reactor with polytetrafluoroethylene, and reacted at 120°C for 24h. After the reaction was completed, it was transferred to a flask, 0.25mL of epichlorohydrin was added, and heated under reflux at 70°C for 4h to complete the cross-linking reaction. Finally, the adsorbent was recovered by centrifugation, and the template cobalt ions were removed by washing with nitric acid. The material was washed with deionized water until neutral, and then vacuum dried to obtain a tetraethylenepentamine functionalized nonionic imprinted polymer SIM-NIP.

[0042] Polyacrylonitrile powder, polyvinyl pyrrolidone and Co(Ⅱ)-SIM-IIP were dissolved in dimethylformamide and stirred at room temperature for 2 hours to prepare electrospinning precursor solution. The electrospinning precursor solution was dried in a vacuum drying oven at 60°C for 6 hours, transferred into deionized water, and polyvinyl pyrrolidone was eluted to obtain ion imprinted membrane material Co(Ⅱ)-PIIMs-x, x=8, 10, 12;

[0043] Polyacrylonitrile powder, polyvinyl pyrrolidone and SIM-NIP were dissolved in dimethylformamide and stirred at room temperature for 2 hours to prepare an electrospinning precursor solution. The electrospinning precursor solution was dried in a vacuum drying oven at 60°C for 6 hours, transferred to deionized water, and the polyvinyl pyrrolidone was eluted to obtain the non-ionic imprinted membrane material PNIMs-10.

[0044] Furthermore, the amount of zinc acetate used is 9.5 g, the amount of 4-methyl-5-imidazolecarboxaldehyde used is 9.5 g, the amount of methanol used is 36 mL, and the amount of tetrahydrofuran used is 72 mL.

[0045] Furthermore, the amount of SIM-1 used is 2.8 g, the amount of cobalt nitrate hexahydrate used is 2.9 g, the amount of tetraethylenepentamine used is 4.0 mL, and the amount of dimethylformamide used is 100 mL.

[0046] Furthermore, the molecular weight of polyacrylonitrile is 150000, the polyvinyl pyrrolidone is K30, the amount of polyacrylonitrile and polyvinyl pyrrolidone is 0.5g, the amount of Co(Ⅱ)-SIM-IIP is any one of 0.5g, 0.7g and 0.8g, and the parameters of electrospinning are: spinning voltage is 18kV, metal needle specification is 20G, casting liquid capacity of two syringes is 2mL, pushing speed is 0.0020mm / s, injection distance is 12cm, and receiving speed is 150r / min.

[0047] Furthermore, the evaluation process of the membrane performance of Co(II)-PIIMs-x comprises the following steps:

[0048] The test was conducted using a membrane flux tester with a cross-flow filtration system. The pressure of the tester was adjusted to 1 bar, and the filter membrane was pre-pressed with deionized water at room temperature for 0.5 h to ensure a stable flux.

[0049] Under the above test conditions, deionized water was passed through the filter membrane for 0.25 h, and the pure water flux of the prepared Co(Ⅱ)-PIIMs-x was determined by collecting the volume of filtered deionized water;

[0050] Under the above pressure conditions, the membrane's Co(II) filtration performance was evaluated at a constant concentration of 50 mg / L of Co(II).

[0051] Furthermore, the adsorption performance of the Co(Ⅱ)-PIIMs-x on cobalt ions is evaluated, comprising the following steps: taking 100 mL of cobalt-containing wastewater with a concentration of 10 mg / L, adjusting the pH value to 5-9 with 1.0 mol / L NaOH solution, and then adding 10 mg of Co(Ⅱ)-PIIMs-x, and adsorbing the cobalt ions in the wastewater at a temperature of 288.15K-318.15K, and the adsorption treatment time is 0-24 hours.

[0052] Furthermore, the pH value of the cobalt-containing wastewater is adjusted to 8.3.

[0053] Furthermore, the adsorption temperature of the Co(Ⅱ)-PIIMs-x is 298.15K.

[0054] Furthermore, the adsorption time of the cobalt-containing wastewater is 12 hours.

[0055] In this embodiment,

[0056] Example 1, please refer to Figure 1 , Figure 1 XRD analysis diagrams of PAN, SIM-1, Co(Ⅱ)-SIM-IIP, SIM-NIP, Co(Ⅱ)-PIIMs-10 and PNIMs-10 prepared in the present invention.

[0057] Example 2, Fourier transform infrared spectroscopy confirmed the formation of SIM-1, at 1,628 cm -1 The characteristic C=O stretch from the aldehyde substituent was observed at 2,928 cm -1 and 2,818cm -1 The CH stretching band at 1496 cm -1 Corresponding to CC, Co(Ⅱ)-SIM-IIP and SIM-NIP at 1,628 cm -1The C=O peak disappears, which is due to the reaction between the aldehyde group of SIM-1 and the amino group of tetraethylenepentamine, located at 2244 cm -1 The CN stretching vibration is the characteristic peak of the PAN film, and the FT-IR graph can further prove that the material was successfully prepared.

[0058] Example 3, please refer to Figure 2 , Figure 2 These are the SEM images of PAN and Co(Ⅱ)-PIIMs-10 prepared in the present invention. Nanofiber morphology is formed on the surface of PAN and Co(II)-PIIMs-10. For the original PAN fiber membrane, it is clearly observed that its surface presents a nanofiber network structure with uniform diameter. The nanofibers are randomly arranged and unevenly arranged. After adding Co(Ⅱ)-SIM-IIP, it can be observed that the PAN membrane carries Co(Ⅱ)-SIM-IIP as a carrier, which is the addition of MOFs.

[0059] Example 4, please refer to Figure 3 , Figure 3 The membrane flux of PAN and Co(II)-PIIMs-x prepared by the present invention is as follows: compared with pure PAN nanofiber membrane, the hydrophilicity of Co(II)-PIIMs-x is increased; when Co(II)-SIM-IIP is added, the contact angle of the membrane material is reduced and the hydrophilicity is increased; since hydrogen bonds are formed between water molecules and the membrane surface, Co(II)-SIM-IIP contains polar groups such as amino groups and has strong hydrophilicity, thereby improving the hydrophilicity of the ion imprinted membrane.

[0060] Example 5, please refer to Figure 4 , Figure 4 The membrane flux and retention rate of PAN and Co(II)-PIIMs-x prepared in the present invention are shown in Figure 2. The membrane flux and retention rate of Co(II)-PIIMs-10 are the highest. When the doping amount is increased to 12%, the voids of the composite membrane are reduced due to the agglomeration of particles, resulting in a decrease in the membrane flux and retention rate of the membrane material.

[0061] Example 6, please refer to Figure 5, take 100mL of 10.0mg / L cobalt-containing solution, adjust its pH value to 5.0~9.0 with 1.0mol / L HNO3 solution, then add 10.0mg of adsorbent PAN, SIM-NIP, Co(Ⅱ)-SIM-IIP, Co(II)-PIIMs-8, Co(II)-PIIMs-10 and Co(II)-PIIMs-12 respectively, and then place it in a 298.15K constant temperature oscillator to adsorb cobalt ions in the wastewater. After oscillating at 150rpm for 12h, take 3ml of supernatant in a 25mL volumetric flask, add 1.0mL of HAc-NaAc buffer solution with a pH of 4.7 and 1.0mL of nitroso-R salt solution with a concentration of 4g / L, make up to volume with distilled water, and measure the adsorption amount by UV-visible spectrophotometer. Figure 5 It can be seen that at pH = 8.3, the adsorption amount of Co(II)-PIIMs-10 is 61.65 mg / g.

[0062] Example 7, please refer to Figure 6 , take 50mL of 10mg / L cobalt-containing solution, adjust its pH to 8.3 with 1.0mol / L NaOH solution, add 10mg of Co(II)-PIIMs-10 or 10mg of PNIMs-10, and then place it in a constant temperature oscillator at 298.15K to adsorb cobalt ions in the wastewater. After oscillating at 150rpm for 10min, 20min, 30min, 60min, 120min, 180min, 240min, 300min, 420min, 480min, and 720min, take out 3mL of supernatant and put it in a 25mL volumetric flask, add 1.0mL of HAc-NaAc buffer solution with a pH value of 4.7 and 1.0mL of nitroso-R salt solution with a concentration of 4g / L, make up to volume with distilled water, and measure the adsorption amount by UV-visible spectrophotometer.

[0063] Example 8, please refer to Figure 7 , take 100 mL of cobalt-containing solutions with concentrations of 5 mg / L, 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, and 60 mg / L, respectively, adjust them to pH 8.3 with 1.0 mol / L NaOH solution, add 10 mg of Co(II)-PIIMs-10, and then place them in a constant temperature oscillator at 298.15 K to adsorb cobalt ions in the wastewater. After oscillating at 150 rpm for 12 h, take 3 mL of supernatant in a 25 mL volumetric flask, add 1.0 mL of HAc-NaAc buffer solution with a pH of 4.7 and 1.0 mL of nitroso-R salt solution with a concentration of 4 g / L, make up to volume with distilled water, and measure the adsorption amount using a UV-visible spectrophotometer.

[0064] Example 9, please refer to Figure 8 100 mL of 10 mg / L cobalt solution was taken, the pH value was adjusted to 8.3 with 1.0 mol / L NaOH solution, and then 10 mg of Co(II)-PIIMs-10 was added, and then placed in the presence of K + , Ca2 + Mg2 + 、Ni + The two-phase mixed solution was subjected to adsorption treatment and after shaking at 150 rpm for 12 h, the supernatant was measured by atomic absorption to calculate the adsorption amount.

[0065] Example 10, please refer to Fig. 9 , take 100mL of 10mg / L cobalt-containing solution, adjust it to 8.3 with 1.0mol / L NaOH solution, add 10mg of Co(II)-PIIMs-10, and then place it in a constant temperature oscillator at 288.15K, 298.15K, 308.15K, and 318.15K respectively to adsorb cobalt ions in the wastewater. After oscillating at 150rpm for 12h, take 3mL of supernatant in a 25mL volumetric flask, add 1.0mL of HAc-NaAc buffer solution with a pH of 4.7 and 1.0mL of nitroso-R salt solution with a concentration of 4g / L, make up to volume with distilled water, and measure the adsorption amount using a UV-visible spectrophotometer.

[0066] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing a Co(II)-PIIMs material for selectively adsorbing cobalt ions, characterized in that: The preparation of the Co(II)-PIIMs material for selectively adsorbing cobalt ions comprises the following steps: Dissolve zinc acetate in methanol, dissolve 4-methyl-5-imidazolecarboxaldehyde in tetrahydrofuran, mix the mixed solution of zinc acetate and methanol and the mixed solution of 4-methyl-5-imidazolecarboxaldehyde and tetrahydrofuran, stir vigorously at room temperature for 24 hours, centrifuge, wash with methanol, and air-dry the obtained SIM-1 at room temperature for 48 hours; Tetraethylenepentamine and cobalt nitrate hexahydrate were dissolved in dimethylformamide, heated under reflux at 70°C for 6h to allow tetraethylenepentamine to fully complex with cobalt ions, and then SIM-1 was added, and after being evenly dispersed, it was transferred to a hydrothermal reactor with polytetrafluoroethylene, and reacted at 120°C for 24h. After the reaction was completed, it was transferred to a flask, 0.25mL of epichlorohydrin was added, and heated under reflux at 70°C for 4h to complete the cross-linking reaction. Finally, the adsorbent was recovered by centrifugation, and the template cobalt ions were removed by washing with nitric acid. The material was washed with deionized water until neutral, and then vacuum dried to obtain tetraethylenepentamine functionalized MOFs cobalt ion imprinted polymer Co(Ⅱ)-SIM-IIP; Polyacrylonitrile powder, polyvinyl pyrrolidone and Co(Ⅱ)-SIM-IIP were dissolved in dimethylformamide and stirred at room temperature for 2 hours to prepare an electrospinning precursor solution. The electrospinning precursor solution was dried in a vacuum drying oven at 60°C for 6 hours, transferred to deionized water, and the polyvinyl pyrrolidone was eluted to obtain the ion imprinted membrane material Co(Ⅱ)-PIIMs-x, x=8, 10, 12.

2. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions according to claim 1, characterized in that: The amount of zinc acetate used is 9.5 g, the amount of 4-methyl-5-imidazolecarboxaldehyde used is 9.5 g, the amount of methanol used is 36 mL, and the amount of tetrahydrofuran used is 72 mL.

3. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions according to claim 1, characterized in that: The amount of SIM-1 used is 2.8 g, the amount of cobalt nitrate hexahydrate used is 2.9 g, the amount of tetraethylenepentamine used is 4.0 mL, and the amount of dimethylformamide used is 100 mL.

4. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions according to claim 1, characterized in that: The molecular weight of polyacrylonitrile is 150000, the polyvinyl pyrrolidone is K30, the dosage of polyacrylonitrile and polyvinyl pyrrolidone is 0.5g, the dosage of Co(Ⅱ)-SIM-IIP is any one of 0.5g, 0.7g and 0.8g, and the parameters of electrospinning are: spinning voltage is 18kV, metal needle specification is 20G, casting liquid capacity of two syringes is 2mL, pushing speed is 0.0020mm / s, injection distance is 12cm, and receiving speed is 150r / min.

5. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions according to claim 1, characterized in that: The evaluation process of the membrane performance of Co(II)-PIIMs-x comprises the following steps: The test was conducted using a membrane flux tester with a cross-flow filtration system. The pressure of the tester was adjusted to 1 bar, and the membrane was pre-pressurized with deionized water for 0.5 h at room temperature to ensure a stable flux. Under the above test conditions, deionized water was passed through the filter membrane for 0.25 h, and the pure water flux of the prepared Co(Ⅱ)-PIIMs-x was determined by collecting the volume of filtered deionized water; Under the above pressure conditions, the membrane's Co(II) filtration performance was evaluated at a constant concentration of 50 mg / L of Co(II).

6. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions according to claim 1, characterized in that: The evaluation of the adsorption performance of Co(Ⅱ)-PIIMs-x on cobalt ions includes the following steps: taking 100 mL of cobalt-containing wastewater with a concentration of 10 mg / L, adjusting the pH value to 5-9 with 1.0 mol / L NaOH solution, and then adding 10 mg of Co(Ⅱ)-PIIMs-x, and adsorbing the cobalt ions in the wastewater at a temperature of 288.15K-318.15K, and the adsorption treatment time is 0-24 hours.

7. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions according to claim 6, characterized in that: The pH value of the cobalt-containing wastewater was adjusted to 8.

3.

8. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions according to claim 6, characterized in that: The adsorption temperature of the Co(Ⅱ)-PIIMs-x is 298.15K.

9. The method for preparing the Co(II)-PIIMs material for selectively adsorbing cobalt ions according to claim 6, characterized in that: The adsorption time of the cobalt-containing wastewater is 12 hours.

Citation Information

Patent Citations

  • Cobalt ion imprinted polymer adsorption material based on MOFs as well as preparation method and application of adsorption material

    CN113150296A